On the use of variability operations in the V‐Modell XT software process line. Issue 4 (30th September 2015) - Kuhrmann, Marco; Méndez Fernández, Daniel; Ternité, Thomas
Abstract: Software process lines provide a systematic approach to develop and manage software processes. It defines a reference process containing general process assets, whereas a well‐defined customization approach allows process engineers to create new process variants, for example, by extending or modifying process assets. Variability operations are an instrument to realize flexibility by explicitly declaring required modifications, which are applied to create a procedurally generated company‐specific process. However, little is known about which variability operations are suitable in practice. In this article, we present a study on the feasibility of variability operations to support the development of software process lines in the context of the V‐Modell XT. We analyze which variability operations are defined and practically used. We provide an initial catalog of variability operations as an improvement proposal for other process models. Our findings show that 69 variability operation types are defined across several metamodel versions of which, however, 25 remain unused. The found variability operations allow for systematically modifying the content of process model elements and the process documentation, and they allow for altering the structure of a process model and its description. Furthermore, we also find that variability operations can help process engineers to compensate process metamodel evolution. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Variability operations are an instrument to realize flexibility in software process lines by explicitly declaring required modifications, which are applied to create a procedurally generated company‐specific process. We present a study on the feasibility of variability operations in the context of the V‐Modell XT. Our findings show that 69 variability operation types are defined across several metamodel versions, which allow for systematically modifying process content and structure and help process engineers to compensate process metamodel evolution.